A new tourism paradigm in the marketplace: armchair travel and destination experiences - Yu, Jongsik; Moon, Hyoungeun; Chua, Bee-Lia; Han, Heesup (SAGE Publications Ltd, 2024)
This study develops a robust theoretical framework in order to explain the effect of destination brand experiences in armchair tourism on the brands’ authenticity and the consumers’ loyalty. The study proposes sensory, behavioral, intellectual, and affective subfactors as the four subfactors of the destination brand experience in armchair tourism. The analytical outcome confirmed that the study’s eight hypotheses were supported. Specifically, destination brand experiences in armchair tourism have a meaningful effect on a brand’s authenticity, which in turn has a significant effect on the tourists’ loyalty. The study’s results successfully demonstrated the importance of the destination brand experience in armchair tourism, and it provides meaningful insights into its positive effect on tourists.